At the limit of the psychic and the law: transgenerationality in family loss of custody cases (2019)
The process for removal of the Family Power withdraw legal authority from careless parents involves children and adolescents in situations of risk, of abandonment, and of domestic violence, as it fails to comply with the Brazilian Statute of Children and Adolescents. In this context, the State intervenes in the family and institutes this process against the parents, that is, the risk of losing legal authority over their children. This study sought to understand what aspects of transgenerational psychic transmission are present in the performance of the parental role of fathers and mothers who were in the eminence of losing custody of their children. This study’s methodology is document research, with the research of legal authority processes between the years 2010-2015 of Joinville County, totaling nine processes. With the analysis of the psychological reports and social studies produced for the judicial processes of withdraw legal authority, evidence of the transgenerational psychic transmission was verified, specifically regarding the forms of intrafamily violence and the process of affective negligence present in the previous history of these parents.